A contribuição do Brasil na mitigação das mudanças climáticas através do valor compartilhado dos investimentos sustentáveis (ESG e Impact Investing) - Loro Netto, Caio César Alvares (2023)
This study is guided by the analysis of legal instruments of international treaties that allow for the protection of sustainable investments, here delimited by those based on Environmental, Social and Governance (ESG) criteria and those intended for projects aimed at promoting positive social and/or environmental impact (impact investments). In addition to the historical context and definitions of sustainable investments from a legal and economic perspective, the approach examines case studies of financing applied to sustainable ventures and their positive outcomes regarding (i) their potential for competitiveness in the medium and long term; (ii) their measurable social and/or environmental impact; and (iii) the corresponding financial return to the investor (shared value). The effectiveness of institutional actions and guidelines promoted by international and Brazilian organizations in fostering sustainable investments are analyzed, particularly those focused on mitigating climate change on a global scale. Finally, this study conducts a comparative study between foreign legal mechanisms for attracting sustainable investments and the Brazilian legal scenario and its public policies for positioning Brazil as a protagonist in contributing to climate change mitigation, especially through the promotion of renewable and sustainable energy generation, including the potential for exporting clean energy, such as through green hydrogen. Using a hypothetical-deductive methodology, the research addresses the issue of demand for climate change mitigation through the hypothesis that sustainable investments can be relevant not only in reducing negative economic initiatives (such as avoiding and reducing carbon emissions) but also in ventures that can be both profitable to the investor and capable of restoring the degraded environment. Thus, the methodological approach examines the political and legal viability of Brazil as a potential leader in the sustainable economy through its attractiveness for investments with this purpose. The production of this study is based on (i) bibliographic analysis; (ii) international, regional treaties, and bilateral investment agreements; (iii) guidelines and reports from international and local intermediary organizations; (iv) foreign legislation for critical-comparative analysis with the Brazilian legal scenario and public policies to attract sustainable investments; (v) sustainability reports and results from investors and sustainable projects (ESG and Impact); and (vi) cases conducted in Arbitration Courts. Based on the analyzed references, which were added to informal interviews with various experts and stakeholders in the Brazilian sustainable investment market, it is noted that there is potential for this market to play a leading role in combating climate change through sustainable investments and generating shared value; nevertheless, it requires catalyzation through a regulatory, supervisory, and standardization framework that promotes the legal certainty demanded by national and, especially, foreign investors